Adubação NPK do tabaco (Nicotina tabacum) num solo da Zona da Mata, Minas Gerais: I — Componentes da produção - Dias Nogueira, Francisco; Ferreira de Novais, Roberto; E O Begazo, José Carlos (Revista Ceres, 2025)
Using the tobacco variety «Chinês» n. 1, a variety grown for its yield of cigar wrapper, the effects of 10 NPK treatments were tested under field conditions at Rio Pomba, MG. The responses measured were: number of leaves per plant, total yield of leaves, yield per class of leaves, and final stand.